Ground Heat Exchanger Modeling Developed for Energy Flows of an Incompressible Fluid - Florides, Georgios A.; Pouloupatis, Panayiotis; Christodoulides, Paul; Lazari, Lazaros (My University, 2012)
Ground-source heat pumps achieve higher efficiencies than conventional air-source heat pumps because they exchange heat with the ground that is cooler in summer and hotter in winter than the air environment. Earth heat exchangers are essential parts of the ground-source heat pumps and the accurate prediction of their performance is of fundamental importance. This paper presents the development and validation of a numerical model through an incompressible fluid flow, for the simulation of energy and temperature changes in and around a U-tube borehole heat exchanger. The FlexPDE software is used to solve the resulting simultaneous equations that model the heat exchanger. The validated model (through a comparison with xperimental data) is then used to extract conclusions on how various parameters like the U-tube diameter, the variation of the ground thermal conductivity and specific heat and the borehole filling material affect the temperature of the fluid
Keywords: Fluids; Energy; Heat pumps; Temperature; Heat exchangers